Directions of the Energy Transition in District Heating: Case Study of Poland - Marian Kampik; Krzysztof Konopka; Damian Gonscz; Wiesław Domański (Energies)
In light of the ongoing discussion concerning the energy transition of the heating sector, primarily focused on district heating and shaped by heating corporations towards an incremental transformation, an alternative direction for the energy transition of the heating sector towards electroheating—a breakthrough transformation—is presented in this paper, along with a justification of its rationale. Arguments “for” and “against” both transformation paths are provided. Analyses of the costs of transforming district heating systems along both trajectories are conducted. The opportunities of a breakthrough transformation are characterized. An alternative approach to the energy transformation of district heating systems will provoke resistance and opposition from representatives of institutions operating within the current model. Transforming the existing heating model without changing its structure will burden society with high transformation costs through demands for government guarantees to cover these expenses. The analysis presented in this paper shows that these costs can be significantly reduced if the approach to the generation and distribution of district heat is changed.